Characterization of Late Polyoma mRNA - Buetti, Elena (1974)
Polyoma-infected mouse kidney cell cultures were labeled with [(3)H]uridine for 3 h late in the lytic cycle (26 to 29 h after infection) and RNA was extracted from cytoplasm and nuclei and from isolated polyribosomes. Sedimentation velocity analysis in sucrose gradients showed that polyoma-specific “giant” and 26S RNAs are present exclusively in the nucleus. RNA associated with cytoplasmic polyribosomes was analyzed by sedimentation in aqueous sucrose density gradients and dimethylsulfoxide sucrose gradients, as well as by polyacrylamide gel electrophoresis. Polyoma-specific RNA in polyribosomes consists of at least two classes, with sedimentation coefficients of 16 (major fraction) and 19S (minor fraction) in aqueous sucrose gradients and 15 and 17S, respectively, in dimethylsulfoxide gradients. Estimates based on dimethylsulfoxide gradient and analysis suggest a molecular weight of approximately 500,000 for 16S RNA and 700,000 for 19S RNA. These polyoma RNAs seem to undergo reversible conformational changes under the different conditions of analysis. We cannot exclude the possibility that they contain more than one molecular species.